2018
DOI: 10.1007/s10620-018-5216-z
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of GPR35 Exacerbates Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: Our experimental data suggest that lack of GPR35 resulted in worsened disease outcome in DSS-induced experimental colitis, indicating that GPR35 could play a crucial role in protecting from colonic inflammation and serve as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
5
42
1
1
Order By: Relevance
“…For example, the GPR35 promoter was found to be the most hypermethylated promoter in sNEC colon compared to non-NEC colon. GPR35 is highly expressed in immune and intestinal epithelial cells, and its loss of function has been shown to promote colitis in an experimental animal model [29]. Similarly, the third most hypermethylated promoter in our data when comparing sNEC colon to control is located upstream of ring finger protein 186 (RNF186), which maintains gut homeostasis by controlling ER stress in colonic epithelium [30].…”
Section: Discussionsupporting
confidence: 55%
“…For example, the GPR35 promoter was found to be the most hypermethylated promoter in sNEC colon compared to non-NEC colon. GPR35 is highly expressed in immune and intestinal epithelial cells, and its loss of function has been shown to promote colitis in an experimental animal model [29]. Similarly, the third most hypermethylated promoter in our data when comparing sNEC colon to control is located upstream of ring finger protein 186 (RNF186), which maintains gut homeostasis by controlling ER stress in colonic epithelium [30].…”
Section: Discussionsupporting
confidence: 55%
“…A genome-wide association study has identified a single nucleotide polymorphism in GPR35 among UC patients [29], potentially linking the regulation of GPR35 to IBD. Recent studies have suggested GPR35 participates in mucosal repair regulation [30,31]. A role of GPR87 in cancer growth and metastasis is emerging too [32,33].…”
Section: Lpa Metabolism and Signalingmentioning
confidence: 99%
“…The pathological changes in the DSS-induced IBD model are similar to human UC. Thus, it is an ideal model that has been widely used to study the mechanism of UC and for screening potential drugs ( Farooq et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%